Implikasi Pernikahan Dini terhadap Kesejahteraan Anak di Kecamatan Jambi Luar Kota Perspektif Maqashid Syariah - Ika Rusmayanti; Yuliatin Yuliatin; Robi’atul Adawiyah (STIKes Ibnu Sina Ajibarang, 2025)
The practice of early marriage persists as a significant societal controversy. Early marriage frequently results in adverse consequences for both the individuals involved and the children subsequently born. Children originating from such unions exhibit an elevated risk of encountering health and developmental challenges, which serve as principal indicators of child well-being. This research endeavors to analyze early marriage and its implications for child welfare through the lens of Family Law. The study aims to contribute novel insights and augment intellectual discourse concerning early marriage and its effects on child welfare. Furthermore, this research ascertains the congruence between the practice of early marriage and the principles of Islamic Sharia pertaining to child welfare. The methodology employed is empirical juridical research utilizing a qualitative approach, incorporating in-depth interviews conducted within the Jambi Luar Kota District. Data collection involved primary and secondary sources, gathered via observation, interviews, and documentation techniques. The study yielded three primary findings: (1) Influential factors contributing to early marriage in the Jambi Luar Kota District encompass: pregnancies compelling marriage, the educational backgrounds of the individuals entering early marriage and their respective parents, personal volition or familial influence and economic circumstances. (2) The repercussions of early marriage within the Jambi Luar Kota District for children include heightened vulnerability to diverse health and social issues, low birth weight, birth-related injuries, growth and developmental impediments such as stunting, and inadequate parental attention leading to hindered cognitive development. (3) From the perspective of Islamic family law, the principles of maqashid sharia demonstrate substantial relevance to child welfare. An ideal marriage necessitates physical, mental, and social preparedness, predicated on the virtuous intention of establishing a family characterized by tranquility (sakinah), affection (mawaddah), and compassion (rahmah).